Bridging the gap between laboratory and application in photocatalytic water purification. Issue 3 (15th January 2019) - Odling, Gylen; Robertson, Neil
Abstract : Despite a large number of publications in the field, photocatalytic water treatment is still somewhat disconnected from real world application and we highlight recent developments to address this. Abstract : Despite a large number of publications in the field, photocatalytic water treatment is still somewhat disconnected from real world application, where there is a clear potential for use. Publications which focus upon overcoming implementation hurdles are often overlooked, but are key in making photocatalytic water purification a reality. This perspective aims to address this, drawing attention to recent developments in materials design, reactor setup and testing methods which take steps towards application beyond the laboratory.